Animals in Contemporary Architecture and Design - Wolch, Jennifer; Owens, Marcus (Humanimalia, 2017)
What are animals doing in design? How do designers see, care for, and use animals? In this paper we analyze an array of design projects featuring animals, identifying intersections between human-animal studies (HAS) and design studies, and discussing the broader social significance of the figure of the animal or animality in design. First, we review the literature at this convergence between these two fields. Next, we discuss the results of our snowball survey of animal design projects across several prominent design blogs. We consider the distribution of attention designers delegate to certain animals, the standardization of certain animal designs, and which designs circulate in the design public sphere, revealing cultural blind spots and biases of designers. Finally, this paper asks how animal design tactics highlight broader social transformations related to the mobilization of perception, behavior and desire as technical practices with functional outcomes. This paper argues that the study of design as a hybrid aesthetic and technical practice yields unique insights both into studies of technics and technology as well as human-animal relations. This paper proposes such a view helps frame both studies of design as well as human relations with nonhuman animals more broadly.